Single-Layer Circularly Polarized Wide Band Reflectarray Antenna with High Aperture Efficiency - Xinyu Da; Jialiang Wu; Jing Zhao; Lin Baoqin; Kai Wu (International Journal of Antennas and Propagation)
A circularly polarized broadband low-cost reflectarray in Ku-band is presented using a novel single-layer subwavelength phase-shifting element. The proposed subwavelength element consists of the concentric split ring and the crossed bowtie. The linear reflected phase response curve with 360° phase coverage is obtained. For experimental verification, an array of 25 × 25 reflectarray prototype has been designed and manufactured by employing the angular rotation technique. The measurements are in good agreement with the simulations. The measured gain at the center frequency of 12.5 GHz is 26.6 dBi, corresponding to the aperture efficiency of 52.5%, and the 1 dB gain bandwidth is 26.4%.